THE ACCULTURATION MODEL OF SECOND LANGUAGE ACQUISITION: INSPECTING WEAKNESSES AND STRENGTHS - Alireza Zaker (Indonesian EFL Journal, 2016)
Previous research has highlighted the significant impact of culture on learning a second language (L2). Accordingly, culture is now believed to be a major learning-affecting factor which, along with linguistic competence, facilitates the process of L2 learning. Some have proposed that being surrounded in the L2 environment gives one a better chance of learning an L2. Based on this premise, Schumann in 1978 proposed the acculturation/pidginization model as an environmental-oriented model that emphasizes identification with a community as the primary requirement of second language acquisition. This study attempts to take a closer look at different aspects of this theory. The taxonomy of factors which control social distance is presented along with the different types of acculturation and the stages/steps of acculturation in an L2 environment. The article concludes with a discussion on the advantages and shortcomings of the model.Keywords: acculturation, culture, pidginization, target language environment